Contextualisation of eLearning Systems in Higher Education Institutions - Gwamba, Gerald; Renken, Jaco; Nampijja, Dianah; Mayende, Godfrey; Birevu Muyinda, Paul (Springer Nature, 2017)
The proliferation of digital technologies, and the emergence of global lifelong learning has steered the transformation of education from the predominant classroom based learning to more flexible technology enhanced learning. However, realizing technology enhanced learning’s much anticipated benefits towards improving the educational potential of Higher Educational Institutions (HEIs) in Developing Countries (DCs) is still a challenge because of the high information systems failure rate. Research suggests potentially substantial misalignment between DC HEIs’ E-Learning Management Systems (ELMS) and their institutional contexts. To explore this gap, this research employs a qualitative approach based on a case study of the Makerere University Electronic Learning Environment (MUELE). We employ the Aparicio eLearning systems theoretical framework to explore the extent to which DC HEIs are aligning their ELMS within their institutional contexts. Results indicate that, ELMS are not aligned to the context of DC HEIs implying that stringent measures need to be taken to close misalignment gaps.
Keywords: E-learning; Learning Management Systems; Higher Education Institutions; Developing Country Context